BIODEGRADATION OF CHLORPYRIFOS BY PSEUDOMONAS DESMOLYTICUM NCIM 2112 - KEDAR B ROKADE; GAJANAN V MALI (International Journal of Pharma and Bio Sciences, 2013)
Chlorpyrifos is an organophosphorus pesticide and widely used in the agricultural field to control beetles, whiteflies, bugs, and flies like insects. This investigation describes the biodegradation of chlorpyrifos by Pseudomonas desmolyticum NCIM 2112. The biodegradation is influenced by other carbon and nitrogen sources and indicates that glucose and maltose are effective at 0.5% concentration and NaNO3 and yeast extract at 0.05%. The pH and temperature optima for degradation was found to be 7.0 and at 300C respectively. Pseudomonas desmolyticum NCIM 2112 degrades chlorpyrifos into non toxic metabolites like 2-pyridinol and thiophosphate.